1988
DOI: 10.1007/bf00381606
|View full text |Cite
|
Sign up to set email alerts
|

Work at sea: a study of sleep, and of circadian rhythms in physiological and psychological functions, in watchkeepers on merchant vessels

Abstract: Daily diary records of sleep and activity, and 4-h measurements of body temperature, performance and subjective alertness were collected on board ship from 15 watchkeepers on the 4-on/8-off system, and from 28 dayworkers, on both westward and eastward transatlantic voyages. The data from a balanced sample of the subjects were analysed over selected 8-d periods of the voyages where four or five time zones were crossed. During these periods the average amount of daily sleep obtained by dayworkers on the eastward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…The results showed that crew members using the former schedule but not the latter one exhibit superposition of 18-h and 24-h periods in all tested variables. Asimilar superposition was also observed in other studies [ 61 , 62 , 66 ]. As the schedule continues, the impact on circadian rhythms becomes more pronounced.…”
Section: Effects Of Non-24-h Conditions On Human Health and Performansupporting
confidence: 88%
See 2 more Smart Citations
“…The results showed that crew members using the former schedule but not the latter one exhibit superposition of 18-h and 24-h periods in all tested variables. Asimilar superposition was also observed in other studies [ 61 , 62 , 66 ]. As the schedule continues, the impact on circadian rhythms becomes more pronounced.…”
Section: Effects Of Non-24-h Conditions On Human Health and Performansupporting
confidence: 88%
“…Naitoh et al [ 65 ] found that a 6-h on/12-h off routine during a nuclear submarine patrol caused a loss of 24-h rhythmicity in oral temperature, which was due not only to a decreased circadian amplitude but also to a dispersion of the time of the peak. A different watch time in three shift groups who used alternative 4-h on/8-h off regimens induced changes in the phase of rectal temperature, noradrenaline excretion, and adrenaline excretion [ 66 ].…”
Section: Effects Of Non-24-h Conditions On Human Health and Performanmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with other industries, marine watchkeeping is influenced by many other factors, such as noise, motion, time zone crossings in navigations associated with rapid changes in longitude, and alterations in daylight length in navigations with significant changes in latitude. These peculiarities, which are inherent to maritime transport, disrupt the operational efficiency of watchkeepers (Condon et al, 1988).…”
Section: Sea Watches On Board and The Circadian Disordersmentioning
confidence: 99%
“…A substantial proportion of people in various occupations undergo rotating working schedules, such as those working in logistics, the catering industry, and international cabin crews. Under certain special conditions, some people are also required to live and work in non-24-h working and rest schedules, such as the non-24-h working schedules with 8 h on and 4 h off (8 h for working and rest, and 4 h for sleep) or 12 h on and 6 h off (12 h for working and rest, and 6 h for sleep), which are prevalently used in maritime operations, oil mining, and some other industries (12)(13)(14)(15)(16)(17)(18)(19)(20). Split-duty schedules might be considered as an alternative to longterm shifting rosters, but the physiologic circadian and diurnal rhythms and, as a consequence, metabolism and performance are also subject to changes under the non-24-h schedules (21).…”
mentioning
confidence: 99%